2015
DOI: 10.1016/j.yebeh.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for reading disability in families with rolandic epilepsy

Abstract: OBJECTIVE The high prevalence and impact of neurodevelopmental comorbidities in childhood epilepsy are now well known, as are the increased risks and familial aggregation of reading disability (RD) and speech sound disorder (SSD) in rolandic epilepsy (RE). The risk factors for RD in the general population include male sex, SSD and ADHD but it is not known if these are the same in RE or whether there is a contributory role of seizure and treatment related variables. METHODS An observational study of 108 RE pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 42 publications
2
23
0
1
Order By: Relevance
“…Seizures occur almost exclusively in sleep at the transition between rapid eye movement (REM) and non‐REM cycles, and may secondarily generalize. Approximately 30% of RE patients have an antecedent history of speech sound disorder (SSD, developmentally inappropriate errors in speech production that limit intelligibility, usually caused by a mild speech dyspraxia), and 42% meet ICD‐10 criteria for reading disorder . RE clinically overlaps with more severe epilepsy syndromes in the “epilepsy‐aphasia spectrum” such as atypical benign partial epilepsy (ABPE, OMIM #604827), continuous spikes in slow wave sleep (CSWSS), and Landau–Kleffner syndromes (LKS, OMIM #245570) as well as atypical forms that all share the common electroencephalographic (EEG) signature of centrotemporal spikes (CTS).…”
Section: Introductionmentioning
confidence: 99%
“…Seizures occur almost exclusively in sleep at the transition between rapid eye movement (REM) and non‐REM cycles, and may secondarily generalize. Approximately 30% of RE patients have an antecedent history of speech sound disorder (SSD, developmentally inappropriate errors in speech production that limit intelligibility, usually caused by a mild speech dyspraxia), and 42% meet ICD‐10 criteria for reading disorder . RE clinically overlaps with more severe epilepsy syndromes in the “epilepsy‐aphasia spectrum” such as atypical benign partial epilepsy (ABPE, OMIM #604827), continuous spikes in slow wave sleep (CSWSS), and Landau–Kleffner syndromes (LKS, OMIM #245570) as well as atypical forms that all share the common electroencephalographic (EEG) signature of centrotemporal spikes (CTS).…”
Section: Introductionmentioning
confidence: 99%
“…2 Behavioral and cognitive impairments are increasingly recognized in BECTS. For example, we found that 67% of children with BECTS have attention impairments, 54% have language impairments, and 42% have reading disability; [3][4][5] our meta-analyses identified moderate effect sizes for reading and language impairments-Cohen's d = 0.7. 3 Speech dyspraxia 6…”
mentioning
confidence: 99%
“…RE is the most common childhood epilepsy, affecting 17%‐25% of children with epilepsy in the 5‐ to 14‐year age range . The syndrome is associated with specific neuropsychological impairments such as in speech and language, literacy, and attention as well as motor coordination deficits but is not associated with autism spectrum disorder or intellectual disability . Our study focused on children of school age (5‐16 years old) with RE, and our protocol is published .…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] The syndrome is associated with specific neuropsychological impairments such as in speech and language, literacy, and attention as well as motor coordination deficits but is not associated with autism spectrum disorder or intellectual disability. [20][21][22] Our study focused on children of school age (5-16 years old) with RE, and our protocol is published. 23 Specifically, our objectives were to review published research to identify outcomes reported in research and to seek consensus on which outcomes were perceived to be most important to measure in research.…”
Section: Introductionmentioning
confidence: 99%